On the Use of Fractional-Order Controllers for Performance Improvements in AC Drives - Mehmood, Chaudhry Arshad; Kavasseri, Rajesh G. (Electric power components and systems, 2015)
Abstract-The control performance of AC electric drives is sensitive to and often degrades with parametric variations. This article proposes the use of fractional-order controllers to combat parameter variations. The speed control of an AC induction motor drive achieved through indirect field-oriented control is considered for illustration. The performance of the proposed controller is compared with a well-tuned proportional-integral controller when critical motor parameters are subject to parametric variations about their nominal values. Dynamic simulations in MATLAB/Simulink (The Math Works, Natick, Massachusetts, USA) are conducted to assess control performance.